Effect of saponin rich lucerne fodder supplementation on rumen fermentation,bacterial and protozoal population in buffalo bulls - MALIK, P K; SINGHAL, K K; DESHPANDE, S B (The Indian Journal of Animal Sciences, 2011)
Saponin content of lucerne (Medicago sativa) fodder at second cut was observed highest (2% on DM basis). Lucerne fodder (II cut) at 30 % level was supplemented to the total mixed ration for investigating the effect on DM intake, rumen fermentation and microbial population in buffalo bulls. Male buffalo bulls (6) were randomly divided into 2 groups of 3 animals each in which group 1 was fed on wheat straw and concentrate (60:40) based TMR-1 while group 2 was fed on lucerne supplemented TMR–2. The intake of saponins through lucerne fodder in group 2 was 47.43 g/d, which did not affect DM intake adversely, and DM intake in group 2 was somewhat higher than recorded for group 1. The saponins of lucerne fodder (II cut, 30 % level in TMR) did not affect the rumen pH, ammonical nitrogen (mg/100 ml) and total volatile fatty acid production (m mol/l) however, acetate and propionate in the TVFA was affected significantly, while the proportion of butyrate remain unaffected by the supplementation. The numbers of bacteria including total, cellulolytic and methanogenic in group 2 was somewhat higher than in group 1 but the variation between both the groups was not significant and saponins through lucerne fodder up to the level of 47 g/d did not affect the bacterial biomass significantly. Protozoal population in the rumen was affected significantly by the saponins of lucerne fodder and about 20 % reduction in protozoal population was observed due to the supplementation of lucerne fodder. Thus, it may be concluded that saponins through lucerne fodder up to the level of 0.60% of DMI can reduce the protozoal population significantly without affecting other rumen biomass, DM intake and fermentability of feed and thereby can increase the productionpotential of ruminants. Therefore, more natural feeds having saponins should be explored along with safe level of their inclusion in the ration.